Practical Application 5S in Selected Factories Automotive Industry - Kamińska, Aleksandra (Studia Oeconomica Posnaniensia, 2016)
Obvious assumptions about the necessity of keeping an orderly workplace, systematized under 5S, can bring both qualitative and environmental benefits to the company. What is more, some enterprises use 5S additionally in order to enhance their market competitiveness. This tool, applied more broadly and for many different reasons in various organizations, is no longer a good practice only, but a powerful company’s management tool. Its performance can be divided into three basic phases: training, implementation and monitoring, which compose a cycle that requires continuous improvement at each stage. The author attempts to depict the way of functioning of 5S method in some automotive factories, along with its limitations.